Insights into the airborne microorganisms in a Sichuan south-road dark tea pile fermentation plant during production - Liu, Miaoyi; Li, Xian; Li, Yimiao; Zou, Yao (Frontiers in Microbiology, 2024)
Introduction Sichuan south-road dark tea (SSDT) is generally produced through a series of processes, including fixing, rolling, pile fermentation, and drying, with microbial action during pile fermentation playing a crucial role in determining tea quality. The air within the SSDT pile fermentation plant (SSDTPP) is considered an important source of these microbes, but research in this area has been limited. Methods In this study, air samples from SSDTPP were collected on the 1st (SSDT1), 12th (SSDT2), and 24th (SSDT3) days of pile fermentation and comprehensively analyzed by high-throughput sequencing. Results and discussion The results revealed the presence of 2 and 24 phyla, 9 and 49 classes, 18 and 88 orders, 28 and 153 families, 38 and 253 genera, and 47 and 90 species of fungi and bacteria, respectively, across all samples. SSDT1 and SSDT2 individually had the highest fungal and bacterial diversity, while Aspergillus was the dominant genus throughout the pile fermentation with an abundance of 34.6%, 91.17%, and 67.86% in SSDT1, SSDT2, and SSDT3, respectively. Microbial populations in SSDT1 were predominantly involved in xenobiotic biodegradation and metabolism, amino acid metabolism, the biosynthesis of other secondary metabolites, etc. However, SSDT2 exhibited a higher prevalence of human disease-related functions. SSDT3 primarily focused on the metabolism of other amino acids and carbohydrate metabolism. Additionally, 104 genera and 22 species coexisted in both SSDTPP air and piled SSDT, suggesting that frequent microbial exchange may occur between them. These findings pave the way for microbial traceability during SSDT production and provide a foundation for further functional microbial research.